Bamboo bio composite: A renewable and sustainable sound absorber for acoustic comfort in indoor settings - Hassan Irvani; Hassan Asilian Mahabadi; Ali Khavanin; Ali Safari Variani; Mohammad Javad SheikhMozafari (Journal of Engineered Fibers and Fabrics)
This investigation aimed to optimize both the structural and acoustic properties of bamboo biocomposite as a sustainable sound absorber through a combination of experimental and modeling approaches. Bamboo composite panels were fabricated with varying structural parameters, including density, thickness, binder concentration, and fiber ratio. Following the optimization of the composite, absorption coefficient calculations were conducted using an impedance tube, along with mathematical models such as Johnson-Champoux-Allard (JCA) and Delany-Bazley (DB). Porosity and airflow resistivity (AFR) parameters were directly determined, while the parameters of tortuosity, viscous, and thermal characteristic length were inversely determined using the differential evolution algorithm in MATLAB. The Field Emission Scanning Electron Microscope (FESEM) was also used for the morphological analysis of the samples. The outcomes revealed a significant increase in Sound Absorption Coefficient (SAC) at various frequencies with the augmentation of density and thickness. For the optimal composite (density: 250 kg/m 3 , thickness: 40 mm, binder concentration: 20%, and fiber ratio F:C = 65:35), the average SAC above 630 Hz was 0.75. Furthermore, the impedance tube results exhibited noteworthy concordance with the predictions of the JCA model. Conclusively, the findings of this research underscore the potential of natural bamboo fiber-based composites as promising sound absorbers for effective sound control in indoor environments.